The content and distribution of 18 phenolic compounds in 462 batches of edible flowers from 73 species commercially available in China. (April 2023) - Li, Ziqing; Zhang, Jianqing; Meng, Qian; Yang, Lin; Qiu, Mingyang; Li, Yun; Yao, Shuai; Wei, Wenlong; Yao, Changliang; Bi, Qirui; Li, Jiayuan; Guo, De-an
Graphical abstract: Highlights: This was the first report to systematically investigate all possible phenolic compounds distributed in almost all edible and medicinal flowers available in Chinese market. A HPLC method was firstly established and validated for simultaneous determination of 18 polyphenols in probably the largest quantity of flower samples as aforementioned. This study offered a bird view of polyphenols and proposed recommendation on flower resource utilization. Abstract: Phenolic compounds are widely distributed in plant flowers. The present study systematically analyzed 18 phenolic compounds, represented by 4 monocaffeoylquinic acids, 4 dicaffeoylquinic acids, 5 flavones and 5 other phenolic acids, in 73 species (462 batches of samples) of edible flowers by a new established and validated HPLC-UV (high-performance liquid chromatography ultraviolet) (327/217 nm) method. Among all the species analyzed, 59 species were demonstrated to contain at least one or more quantifiable phenolic compounds, especially in families of Composite, Rosaceae and Caprifoliaceae. 3-Caffeoylquinic acid was found to be the most ubiquitous phenolic compound (in 193 batches of 73 species with the content between 0.061 and 65.10 mg/g), followed by rutin and isoquercitrin. While sinapic acid, 1-Caffeoylquinic acid and 1, 3-dicaffeoylquinic acid (only in 5 batches of 1 specie with the content between 0.069 and 0.12 mg/g) were the least ones both in ubiquity and concentration. Additionally, the distribution and abundances of phenolic compounds were compared between these flowers, which would be valuable for auxiliary authentication or other usages. This research covered almost all edible and medicinal flowers in the Chinese market with 18 phenolic compounds therein quantified, which delivered a bird view of phenolic compounds in a broad perspective of edible flowers.